2005
DOI: 10.1177/152692480501500207
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Organ Donation Behavior among Hispanic Americans

Abstract: The data provide a springboard for larger studies encompassing the diversity and geographical dispersion of Hispanic Americans. The data also highlight the importance of educational efforts to make Hispanic Americans aware of people in their community who have donated in the past or who are now potential donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 19 publications
6
30
0
Order By: Relevance
“…One of the few studies to examine risk factors for organ donation in Hispanic American individuals in Arizona found that family discussions about organ donation and knowing someone willing to be a donor were significant predictors for the willingness to be an organ donor 11. Similarly, we found that family influence was important and, when present, a participant was 2 times as likely to be an organ donor.…”
Section: Commentsupporting
confidence: 68%
See 1 more Smart Citation
“…One of the few studies to examine risk factors for organ donation in Hispanic American individuals in Arizona found that family discussions about organ donation and knowing someone willing to be a donor were significant predictors for the willingness to be an organ donor 11. Similarly, we found that family influence was important and, when present, a participant was 2 times as likely to be an organ donor.…”
Section: Commentsupporting
confidence: 68%
“…Similarities exist in both minority groups, such as distrust of the medical system and misconceptions concerning religion; however, there are other critical issues specific to the Hispanic American community. Important issues identified to affect organ donation rates in Hispanic American individuals include language barrier, involvement of the extended family in decision making, lack of knowledge and/or misconceptions concerning organ donation, religious beliefs and/or cultural viewpoints, and failures of health care professionals to communicate effectively 3,5,1115. Also unique to Hispanic American individuals, they are a highly mobile population, with a constant influx of newcomers both from other communities within the United States and their country of origin 3.…”
Section: Commentmentioning
confidence: 99%
“…Noteworthy is the lack of a relationship between the perception of health care in Spain and the will to donate, present in many studies (9,13,14,23), although it seems clearly conditioned by the scarce representation of the layers of negative ratings. However, and with regard to the informative variables, the will to donate in the immigrant population also varies as a function of diverse aspects of the available information on the topic, underscoring the perception of efficacy, direct knowledge, and the existence of qualified information as the elements most closely linked to a positive disposition, and also following the general tendencies previously found in this field (20,40,(49)(50)(51). The results obtained through multivariate analysis reinforce the evidence of the predictive power of religious beliefs on the disposition to donate and define differentiated groups that are somewhat homogeneous internally in this aspect, grouping the beliefs that already appeared as the most reluctant in the bivariate analysis (practicing Muslims, Buddhists, and Jews).…”
Section: Discussionmentioning
confidence: 98%
“…Hispanic Americans pose a unique challenge mostly for demographic reasons. Over the past decade, the number of Hispanic Americans added to this waiting list has increased by over 260%, while the list involving non-Hispanics has grown 146% 20. This growth in the Hispanic American transplant waiting list parallels the growth of the Hispanic American population as a whole.…”
Section: Discussionmentioning
confidence: 99%